Environmental management of organic waste: State of the art of composting generation from solid waste of the grease and oil trap systems - González-Jiménez, Yuliana (2021)
The wrong disposal of waste brings with it a series of negative environmental impacts for both humans and biota in general. One of the municipal waste that represents the main source of environmental impact and risk in traditional landfills is the biodegradable organic fraction, especially residues from grease and oil traps. The techniques for its decrease in landfills is establish from biodiesel generation to composting. The present study, is a description of the state of the art of some methodologies used worldwide to carry out the composting of the residues of grease and oil traps. It was determined that due to the usual weather conditions in our country, it is possible to use composting processes in the treatment of solid waste from grease and oil trap systems.